STATISTICAL ANALYSIS OF EVALUATION OF THE VOLUME OF THE HIDDEN ECONOMY IN THE REPUBLIC OF UZBEKISTAN (Academicia Globe: Inderscience Research, 2022)
In recent years, many scientists are trying to systematize the methods of statistical measurement of the shadow economy. However, to date, a clear system of signs has not been developed that allows classifying methods for assessing the shadow economy. The purpose of this article is to analyze the most common statistical methods of the shadow economy and try to classify them.